Complement regulatory proteins: Candidate biomarkers in differentiating tuberculosis pleural effusion - Tang, Huan; Hu, Xinyue; Li, Li; Deng, Shuanglinzi; Jiang, Yuanyuan; Luo, Lisha; Cai, Runjin; Yang, Yifei; Wu, Chendong; Gong, Xiaoxiao; Feng, Juntao (Frontiers in Immunology, 2023)
Background and aims: Complement activation is critical for tuberculosis pleural effusion. However, little is known about the diagnostic value of complement regulatory protein (sCD46, sCD55, and sCD59) in differentiating tuberculosis. Materials and Methods: ninety-nine exudative pleural effusion patients were enrolled from the Xiangya Hospital between June 1, 2021, and November 14, 2022. The expression levels of sCD46, sCD55, and sCD59 in pleural effusion were quantified by enzyme-linked immunosorbent assay, and a ROC curve was conducted to evaluate the diagnostic value and combine the diagnostic value of sCD46, sCD55, and sCD59. Results: ADA level in TPE patients is higher than non-TPE patients. It is well-found that TPE patients had lower levels of sCD46, sCD55, and sCD59 compared with non-TPE patients. Moreover, the expression of sCD46, sCD55, and sCD59 in pleural effusion was negatively correlated with ADA. In addition, sCD46, sCD55 and sCD59 existed similar effective diagnostic value as ADA evaluated by AUC were 0.896, 0.857, 0.858 and 0.893, respectively. Furthermore, combine detection of sCD46, sCD55, sCD59 and ADA improved the diagnostic accuracy. Conclusions: sCD46, sCD55, and sCD59 can be used as candidate biomarkers for the diagnosis of TPE. Combine detection with ADA had a better diagnostic value in TPE. Keywords: complement, sCD46, sCD55, sCD59, tuberculosis pleural effusion.